2020
DOI: 10.1136/bmjgh-2020-002801
|View full text |Cite
|
Sign up to set email alerts
|

Global health education in UK medical schools: a review of undergraduate university curricula

Abstract: IntroductionIn recognition of our increasingly globalised world, global health is now a required component of the medical school curriculum in the UK. We review the current provision of global health education (GHE) in UK medical schools to identify gaps in compulsory teaching.MethodsWe conducted a review of the literature to inform a two-part electronic survey of global health compulsory teaching, optional teaching and pre-elective training. Surveys were sent to all 33 UK medical schools for completion by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
(65 reference statements)
0
8
0
1
Order By: Relevance
“…We developed an electronic survey targeted at Newcastle Medical School alumni who have undertaken the SSC in Global Health using SurveyMonkey, an online survey development platform. Survey questions were informed by the study of participants on the University of Wisconsin International Health Fellowship Program (IHFP) (Ramsey et al, 2004), identified by MEDLINE searches, including the terms 'global health' and 'career influence', as well as the survey of GHE in UK medical schools (Matthews, Davies and Ward, 2020). The survey included questions about advanced training and speciality choice, extracurricular activity, postgraduate qualifications, international work, and the Global Health SSC's influence on their clinical practice and careers.…”
Section: Survey Designmentioning
confidence: 99%
See 2 more Smart Citations
“…We developed an electronic survey targeted at Newcastle Medical School alumni who have undertaken the SSC in Global Health using SurveyMonkey, an online survey development platform. Survey questions were informed by the study of participants on the University of Wisconsin International Health Fellowship Program (IHFP) (Ramsey et al, 2004), identified by MEDLINE searches, including the terms 'global health' and 'career influence', as well as the survey of GHE in UK medical schools (Matthews, Davies and Ward, 2020). The survey included questions about advanced training and speciality choice, extracurricular activity, postgraduate qualifications, international work, and the Global Health SSC's influence on their clinical practice and careers.…”
Section: Survey Designmentioning
confidence: 99%
“…The most common organisation students were involved in was Students for Global Health (formerly Medsin) (Table 4). This is perhaps the most prominent student global health network in the UK, which as of 2014-2015, was found to be established and active at 28 (85%) of 33 UK medical schools (Matthews, Davies and Ward, 2020). Since completing medical school, 16 (46%) of 35 respondents indicated they were involved with extracurricular activities.…”
Section: Extracurricular Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in global health has increased among undergraduate students, medical students, and residents, [1][2][3] including neurology residents, [4] likely reflecting the growing burden of neurological disease in low-and middle-income countries. [5][6] However, formalized global neurology training tracks [7] and curricula are rare, [8] with only one-half of US and Canadian neurology programs offering global health electives, [4] thus potentially limiting resident training and exposure to the field.…”
Section: Introductionmentioning
confidence: 99%
“…The UK's General Medical Council (GMC) states that graduates must "evaluate the determinants of health and disease and variations in healthcare delivery and medical practice from a global perspective and explain the impact that global changes may have on local health and wellbeing" [4]. However, there is variability in global health teaching and no standardised curriculum that all UK medical students cover [5]. Without international electives, a key opportunity to meet this outcome is lost.…”
mentioning
confidence: 99%